"Leader" and "leadership": semantic shades and alternatives in translation (Eurasian Journal of Philology Science and Education, 2023)
The article reveals and scientifically explains the meaning of such concepts as leader and leadership, figure, state figure, political leader, as terms in the field of political linguistics, as a separate field of linguistics. The meanings of these words in various languages, in particular, in European and Russian languages, their semantic nuances and currently existing equivalents in the Kazakh language are analyzed. Internet dictionaries are used for this purpose, i.e. https://www.lugat.kz / - materials of the Kazakh dictionary complex. It is established that some words have been successfully translated, some translations are unsuccessful, some words are translations of several words, i.e. there are repetitions. It was revealed that the literary equivalents of some words have not been stabilized or codified yet.The type of style in which leaders' speeches are often published is the journalistic style of literary language. Recently, as an equivalent of the term "publicistic style", some scholars suggest the translation "kosemsoz". However, the author does not support the use of this alternative translation, for this, the facts are presented as evidence.In order to supplement and clarify the problem raised in the article, the identification of the language environment in Kazakhstan was proposed, in order to be able to more clearly reveal some linguistic aspects related to the concepts of leader and leadership. Of course, already existing classifications were taken into account. The language of Kazakh statesmen and political leaders was classified for the first time taking into account the social aspect of linguistics.Keywords: leader, leadership, linguistic personality, political linguistics, journalistic style, language of a statesman, language of a political leader, language identification.